Uso de mistura de raças de C. lindemuthianum na avaliação da antracnose no feijoeiro - Falleiros, Margot Okagawa (2016)
Wide pathogenic variability of the fungus Colletotrichum lindemuthianum has made it difficult to obtain cultivars with durable resistance to anthracnose in common bean. Assessments by artificial inoculation of different races can be unviable in common bean breeding program since many physiological races have been found. An alternative is using mixture of isolates from different races. However, there are scarce information about the efficiency of this method in the selection of resistant common bean plants and the virulence of pathogen isolates mixture. Thus, the aim of this study was to assess the severity of anthracnose in common bean through inoculation of races 65, 73 and 81 of C. lindemuthianum individually and in mixture, and compare the virulence of isolates/mixture. Two experiments were conducted, both in completely randomized design with Split plot. Isolates were inoculated individually as well in a mixture of the three races (M1) and also obtaining mixtures of the 1 st (M2 and M3) and 2 nd (M4, M5, M6 and M7) generations, in the cultivars Pérola and Majestoso. Area under the disease progress curve (AUDPC) and scores of the severity at 10 days after inoculation were evaluated. The isolates/mixtures were characterized as to mycelial compatibility, sporulation rate and percentage of germination and conidial anastomosis tubes (CATs). From the results obtained, it was evidence that the mixture of races of C. lindemuthianum was efficient in evaluating the severity of anthracnose and most mixtures of races of C. lindemuthianum were more virulent than the races individually.